GST-PRIME: a genome-wide primer design software for the generation of gene sequence tags - Varotto, Claudio (Oxford University Press, 2001)
The availability of sequenced genomes has generated a need for experimental approaches that allow the simultaneous analysis of large, or even complete, sets of genes. To facilitate such analyses, we have developed GST-PRIME, a software package for retrieving and assembling gene sequences, even from complex genomes, using the NCBI public database, and then designing sets of primer pairs for use in gene amplification. Primers were designed by the program for the direct amplification of gene sequence tags (GSTs) from either genomic DNA or cDNA. Test runs of GST-PRIME on 2000 randomly selected Arabidopsis and Drosophila genes demonstrate that 93 and 88% of resulting GSTs, respectively, fulfilled imposed length criteria. GST-PRIME primer pairs were tested on a set of 1900 Arabidopsis genes coding for chloroplast-targeted proteins: 95% of the primer pairs used in PCRs with genomic DNA generated the correct amplicons. GST-PRIME can thus be reliably used for large-scale or specific amplification of intron-containing genes of multicellular eukaryotes.